Theoretical and experimental study on constant volume heating of CO2 by solid propellant. (September 2022) - Chen, Dong; Lin, Zhang; Yao, Hongxin; Ni, Qing; Ye, Hong
Highlights: Solid propellant for the heating of carbon dioxide was proposed. The effects of burning and arrangement modes were analyzed. Solid propellant is effective in shortening the reaction time of launch devices. Abstract: Supercritical carbon dioxide (S-CO2 ) is a potential working medium for pneumatic launch because of its high working capacity. The key to realizing the S-CO2 launch lies in the rapid and efficient heating of liquid CO2 to S-CO2 . We propose using a solid propellant for the rapid heating of CO2 due to its high burning rate and high energy density. To study the effects of constant volume heating CO2 by the propellant, a numerical simulation was performed and experimentally verified. To optimize the heating performance, the effects of radial and axial burning modes, axial and circumferential arrangements, and ambient air temperature on pressure and phase change of CO2 were analyzed. For fixed mass and burning rate, propellant burning radially produces higher pressure and more S-CO2 at the end of combustion than that burning axially. When burning radially, propellants arranged axially produces more S-CO2 than that arranged circumferentially. The pressure and mass of S-CO2 at the end of combustion increase with the ambient air temperature. To achieve a reliable and efficient heating, CO2 should be stored at a constant temperature and the solid propellants should be axially arranged and radially burned.